Solvent-free cycloaddition of CO2 and propylene oxide to cyclic carbonates using different ligand metal complexes - Narang S.; Mehta R.; Upadhyay S.N. (My University, 2025)
Tetradentate ligand metal complexes salen-Co(III)OBzF5, salen-CH3Co(III)OBzF5, salen-CH3Co(III)Br, and salen-ClCo(III)Br were synthesized. These complexes were used as catalysts for the chemical fixation of CO2 and propylene oxide to cyclic carbonates. Tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, [PPN]+CCl- ([PPN]+ D bis(triphenylphosphine)iminium), and tetrabutyl ammonium bromide were used as co-catalysts in the reactions. Additionally, the catalytic activity of naphthen-CoSO4 and salen-CoSO4 was also explored using the above co-catalysts. The conversion of propylene oxide to cyclic carbonate was found to increase with increase in temperature and pressure of carbon dioxide. It was noted that cyclic carbonate product could be obtained at a temperature as low as 60°C and pressure of 20 bar in just 2 h. Further, it was observed that introduction of electrondonating methyl substituent increased the nucleophilic character of the catalyst and reaction conversion. On the contrary, electron-withdrawing substituents like chlorine decreased the cyclic carbonate conversion, thereby making it a weaker nucleophilic catalyst. © 2017 Taylor & Francis Group, LLC.